Screening of Reference Genes for RT-qPCR in Chicken Adipose Tissue and Adipocytes - Na, Wei; Wang, Yuxiang; Gong, Pengfei; Zhang, Xinyang; Zhang, Ke; Zhang, Hui; Wang, Ning; Li, Hui (Frontiers in Physiology, 2021)
RT-qPCR is the most commonly used method to detect gene expression levels. In experiments, it is often necessary to correct and standardize the expression level of target genes with reference genes. Therefore, it is very important to select stable reference genes to obtain accurate quantitative results. Although application examples of reference genes in mammals have been reported, no studies have investigated the use of reference genes in studying the growth and development of adipose tissue and the proliferation and differentiation of adipocytes in chickens. In this study, GeNorm, a reference gene stability statistical algorithm, was used to analyse the expression stability of 14 candidate reference genes in the abdominal adipose tissue of broilers at 1, 4, and 7 weeks of age, the proliferation and differentiation of primary preadipocytes, as well as directly isolated preadipocytes and mature adipocytes. The results showed that the expression of the TBP and HMBS genes was most stable during the growth and development of abdominal adipose tissue of broilers, the expression of the PPIA and HMBS genes was most stable during the proliferation of primary preadipocytes, the expression of the TBP and RPL13 genes was most stable during the differentiation of primary preadipocytes, and the expression of the TBP and HMBS genes was most stable in directly isolated preadipocytes and mature adipocytes. These results provide reference bases for accurately detecting the mRNA expression of functional genes in adipose tissue and adipocytes of chickens.